Peculiarities of the interneuronal pool influence on the spinal motoneurons under the conditions of prolonged hypoestrogenemia - Tkachenko, S. S.; Rodynskyi, O. H.; Rodynska, H. О.; Horb-Havrylchenko, I. V. (Zaporozhye Medical Journal, 2019)
The purpose of research is to study the peculiarities of the interneuronal networks influence on the activity of spinal anterior horns motoneurons under the conditions of experimental menopause. Materials and methods. The study was performed on 51 mature Wistar rats (females). Menopause was induced by a minimally invasive ovariohysterectomy. L5 dorsal root was stimulated by single and paired square-wave impulses. The response was recorded on the dorsal surface of the spinal cord and the ventral root at the same level. Results. An increase in the excitation threshold of the spinal cord afferent fibers and the latent period of 102.14 % and 94.12 %, respectively, were established in animals after ovariectomy. Supramaximal stimulation of the dorsal root L5 induced an increase in the amplitude of components N1 by 10.14 %, N2 by 11.82 %, N3 by 48.28 %, and P-wave by 31.58 %, and the duration of N3 component was increased by 26.54 % in the experimental group. In stimulation by paired pulses over a time interval of 2 ms to 3 ms, a significant increase was observed, and from 6 ms to 100 ms there was a suppression of the N1 component of the second PDP in the group of animals with experimental menopause. The threshold for excitation of motoneurons was decreased to 54.17 ± 19.80 %, the latent period was decreased to 85.39 ± 2.63 %, and the response amplitude was reduced to 127.59 ± 3.78 %. When paired stimuli were applied, there was delayed recovery of evoked response amplitude in the same range (2–100 ms) as in the interneuronal pool study and matching the positive component of potential duration of the spinal cord dorsal surface. Conclusions. Thus, the overall effect of the long-term estrogen deficiency is an increase in the spinal cord motoneurons excitability, facilitation of nerve transmission in the structures of the anterior and posterior horns at high-frequency of dorsal root stimulation, and marked inhibition of low-frequency input due to deepening of the presynaptic inhibition processes mediated by significantly increased activity of substantia gelatinosa neurons.